Stretching the Metaverse Service For The Banking Industry In South Kalimantan: Stretching the Metaverse Service For The Banking Industry In South Kalimantan - sandi alfianur, sandi alfianur; astina bianka, astina bianka (UMBanjarmasin, 2022)
Metaverse is a computer-based technology that aims to make concepts or ideas like the real world, metaverse itself is expected to be used to carry out various kinds of transactions and interactions between humans and computers. metaverse itself is a three-dimensional virtual space that is currently making a lot of people curious both from its very rapid development and its implementation which has started to be widely used. This study aims to determine the existing metaverse industry in South Kalimantan, and this study uses a qualitative narrative method. Currently there are no Islamic banks that use the metaverse and not all conventional banks use this metaverse. Currently, the banking world itself is in the development stage to enter the metaverse because it will make banking transactions easier.